Pengaruh Model Pembelajaran Thinking Aloud Pair Problem Solving (TAPPS) Terhadap Kemampuan Pemecahan Masalah Matematika pada Materi Bentuk Aljabar - Intan Rachmawati; Baidowi Baidowi; Nurul Hikmah; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine the effect of Thinking Aloud Pair Problem Solving (TAPPS) learning model on mathematical problem solving abilities in the form of algebra material. This type of research is a quasi experiment with the posttest only design with a nonequivalent group. The population in this study were 7th grade students of SMPN 1 Mataram in the academic year of 2019/2020. Sample determination using purposive sampling technique, where the sample of this study is students of class VII-I as an experimental class and students of class VII-H as a control class. In the experimental class applied the TAPPS learning model and control class applied the direct learning model. The instrument used in this study was a test of mathematical problem-solving abilities (posttest) on algebra form material. Quantitative data analysis was performed using t-test. The results of the data analysis showed that there are significant differences in students' mathematical problem solving abilities between the classes that get the TAPPS learning and direct learning. This suggests that learning with the Thinking Aloud Pair Problem Solving (TAPPS) model affects the ability to solve mathematical problems in the form of algebra material.